2017
DOI: 10.18235/0000899
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Relationship Violence in Brazil and Honduras

Abstract: Design and layout:Promundo Founded in Brazil in 1997, Promundo works to promote gender equality and create a world free from violence by engaging men and boys in partnership with women and girls. Promundo is a global consortium with members in the United States, Brazil, Portugal, and Democratic Republic of the Congo that collaborate to achieve this mission by conducting cutting-edge research that builds the knowledge base on masculinities and gender equality; developing, evaluating, and scaling up high-impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…In Brazil, violence related to jealousy is still socially accepted as a defense of male honor and as maintenance of female submission (Costa et al, 2016). In a study with Brazilian and Honduran samples, the authors found that controlling the partner's behaviors, such as monitoring the telephone and social networks, choosing clothes, and restricting friendships were common (Taylor et al, 2017). Furthermore, jealousy and fear of infidelity are among the main risk factors in intimate relationships between young people, supported by nonprescribed norms that naturalize and consolidate inequitable gender roles, as well as forced sex (Taylor et al, 2017).…”
Section: Femicide In Brazil and Sociocultural Conditionsmentioning
confidence: 99%
“…In Brazil, violence related to jealousy is still socially accepted as a defense of male honor and as maintenance of female submission (Costa et al, 2016). In a study with Brazilian and Honduran samples, the authors found that controlling the partner's behaviors, such as monitoring the telephone and social networks, choosing clothes, and restricting friendships were common (Taylor et al, 2017). Furthermore, jealousy and fear of infidelity are among the main risk factors in intimate relationships between young people, supported by nonprescribed norms that naturalize and consolidate inequitable gender roles, as well as forced sex (Taylor et al, 2017).…”
Section: Femicide In Brazil and Sociocultural Conditionsmentioning
confidence: 99%
“…It then discusses the results of my study in light of previous research findings before concluding with suggestions for future research that focuses on gaining a better understanding of and preventing Technology-Facilitated IPV (TFIPV) among youth. exceptions including the work of Oliveira, Assis, Njaine, andOliveira (2011), Instituto Avon/Data Popular (2014), Énois I Inteligência Jovem, Instituto Vladimir Herzog, & Instituto Patrícia Galvão (2015) and more recently Campeiz (2018) and Taylor et al (2017Taylor et al ( , 2019. There are a few studies in Brasil focused on the prevention of IPV and gender-based violence more broadly among youth, for example, the work of Murta et al (2013Murta et al ( , 2019Murta et al ( , 2020, Taylor et al (2017) and Viza, Sartori, & Zanello (2017).…”
Section: Introductionmentioning
confidence: 99%
“…exceptions including the work of Oliveira, Assis, Njaine, andOliveira (2011), Instituto Avon/Data Popular (2014), Énois I Inteligência Jovem, Instituto Vladimir Herzog, & Instituto Patrícia Galvão (2015) and more recently Campeiz (2018) and Taylor et al (2017Taylor et al ( , 2019. There are a few studies in Brasil focused on the prevention of IPV and gender-based violence more broadly among youth, for example, the work of Murta et al (2013Murta et al ( , 2019Murta et al ( , 2020, Taylor et al (2017) and Viza, Sartori, & Zanello (2017). In Australia, youth IPV was addressed in prevention research, including the work of Flood (2019) guiding the engagement of men and boys for preventing violence against women and girls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations